Leray-Schauder results for multivalued nonlinear contractions defined on closed subsets of a Fréchet space - Ravi P. Agarwal; Donal O'Regan (International Journal of Mathematics and Mathematical Sciences)
New Leray-Schauder results are presented for multivalued contractions defined on subsets of a Fréchet space E. The proof relies on fixed point results in Banach spaces and on viewing E as the projective limit of a sequence of Banach spaces.